John Ray: “Divinity is my Profession” - Drozdek, Adam (Studia Theologica Varsaviensia, 2022)
Summary. John Ray was primarily interested in his work as a naturalist. However, prompted by his conscience and the sense of his priestly obligation, he authored three books of religious character: one on physico-theology, one on sacred physics, and one on practical theology. The article presents some of his views expressed in these books.